Work and personal e‐mail use by university employees: PIM practices across domain boundaries. Issue 5 (1st April 2013) - Capra, Robert; Khanova, Julia; Ramdeen, Sarah
<x xml:space="preserve">Abstract</x> In this article, we present findings from a survey of nearly 600 university employees' e‐mail use. The study provides a detailed comparison of use patterns between work and personal e‐mail accounts. Our results suggest that users engage in more "keeping" behaviors with work e‐mail than with personal e‐mail—respondents reported more frequent use of keeping actions and larger inbox sizes for their work accounts. However, we found correlations between individual respondents' e‐mail behaviors in the two contexts, indicating that personal preferences can play a role. We also report results pointing to e‐mail as an important boundary management artifact. We show evidence that the use of multiple e‐mail accounts may be a work‐personal boundary placement strategy, but also observe that a fair amount of boundary permeation occurs through e‐mail. To our knowledge, this study is one of the first to compare e‐mail use in both work and personal contexts across the same sample. Our findings extend prior research on personal information management regarding e‐mail use, and help inform the role of e‐mail in managing work‐personal boundaries. The results have implications for the design of e‐mail systems, organizational e‐mail policies, user training, and understanding the impacts of technology on daily life.